F-region electron density and Te / Ti measurements using incoherent scatter power data collected at ALTAIR - Milla, Marco (2006)
The ALTAIR UHF radar was used in an incoherent scatter experiment to observe the low-latitude ionosphere during the Equis 2 rocket campaign. The measurements provided the first high-resolution electron density maps of the low-latitude D- and E-region in the Pacific sector and also extended into the F-region and topside ionosphere. Although the sampling frequency was well below the Nyquist frequency of F-region returns, we were able to estimate Te/Ti ratio and infer unbiased electron density estimates using a regularized inversion technique described here. The technique exploits magnetic aspect angle dependence of ISR cross-section for Te>Ti.